Olahraga chi lebih baik daripada kardio steady-state intensitas rendah untuk meningkatkan kebugaran fisik dan kualitas tidur pada orang tua - Andriana, Laily Mita; Nurdianto, Arif Rahman (Universitas Nusantara PGRI Kediri, 2022)
The condition of elderly is a condition with decreased function both anatomically and physiologically. The problem is the lack of participation of the elderly in exercise due to motivational factors, physical conditions, and attitudes of the elderly towards this type of exercise. This study aims to prove that tai chi is better than low-intensity steady-state cardio in improving the physical fitness and sleep quality of the elderly. The method used in this study is quantitative inferential using a two-group experimental design. This study examined as many as 40 older adults as subjects. The Physical fitness was collected using a senior fitness test instrument, and sleep quality was collected using a sleep quality questionnaire entitled the Pittsburgh Sleep Quality Index. The data analysis technique was paired sample t-test and independent t-test. The results showed that tai chi exercise was better than low-intensity steady-state cardio for increasing flexibility (p<0,05), muscle strength in the upper and lower extremities (p<0,05), and improving coordination and balance abilities (p<0,05). At the same time, the low-intensity steady state is better than tai chi exercise in improving cardiovascular ability (p<0,05). Tai chi exercise is better than the low-intensity steady-state cardio method for improving sleep quality (p<0,05). The conclusion is that tai chi exercise is better than the low-intensity steady state in improving physical fitness and sleep quality in the elderly group.